El uso de los recursos didácticos en el proceso de enseñanza - aprendizaje. - Gamboy Soria, María Gabriela (2018)
The present project is focused on the use of the Didactic Resources in the teaching-learning process at "Jorge Icaza" Educative Unit, which is located in Latacunga, Cotopaxi province. The problem emerged after the analysis of the current teacher’s panorama in the educational work to adapt to the demand of the new education curriculum and the teacher's work overload. These have led teachers not planning their class with the use of teaching resources, causing monotonous teaching and little interest in the student. For this reason, the objective of this research is to analyze the use of didactic resources in the teaching-learning process by teachers. The beneficiaries are the teaching staff, students and parents of the institution. The methodology used was a quantitative approach, the method was the empirical and the level of the research was descriptive and bibliographic. It allowed to analyze the data independently on the variables. The instruments applied were the interview which were applied to authorities and surveys to teachers. The results show that the teacher does not use the teaching resources frequently due to the overload of curricula documentation and the lack of economic resources of the teacher for its design. These factors are those that affect the non-use of teaching resources in the classroom and it has caused that students do no learn significantly and lost interesting in learning. It is concluded that the teacher simply uses the text and the blackboard as resources in all classes and it is vital to mention that today the use of teaching resources is essential in the assimilation of students’ knowledge.